Sustainability in the Design of an Itinerant Cultural Exhibition. Study of Two Alternatives - Natalia Muñoz-López (MDPI AG, 2021)
The sustainability improvement of museums and exhibitions is a recent concern for multiple organisations. The application of sustainability criteria is one of the most important strategies of innovation in design activities, products, and service systems. This study analyses the sustainability of two alternatives to an itinerant cultural exhibition service. The exhibition travels to 12 destinations over 3 years and is within a space of 300 m2. In the first alternative, the contents are printed and exposed on a physical medium, and in the second, audiovisual media projects the contents on the walls. Life cycle sustainability assessment is applied to evaluate the impacts in the environmental dimension and the economic and social dimensions. The calculation of indicators, such as the greenhouse gas emissions, total costs, and working time, which are referred to each sustainability dimension, is conducted. A descriptive, comparative study was performed to identify the impact factors with a higher incidence. The results demonstrate that the audiovisual exhibition is more sustainable than the printed exhibition, with a difference of 8.7%, 7%, and 6.6% in GWP100, CE, and TW indicators, respectively.